Desenvolvimento de reator eletrocinético para aplicações ex-situ - Rocha Júnior, Edvaldo Rodrigues da (Universidade Federal Rural do Semi-Árido, 2018)
The electrokinetic technique has many applications, one of them is the removal of contaminants from the soil. In the electrokinetic process, low intensity electric current is generated due to the application of a potential difference through electrodes inserted in moist soil. An electrokinetic reactor was developed and tested in laboratory with samples of non-artificial soils, whose voltage, current, pH, conductivity and concentrations of chemical elements were analyzed to identify the influence of the use of stainless steel electrodes with a saline electrolyte. Among the methodological procedures, experiments were carried out to evaluate the relationship of voltage variation to 10, 15 and 20 volts, with treatment time of 24, 36 and 48 hours. It was observed the increase of iron, nickel and chromium concentrations in the liquid of the anode reservoir and in the soil, as a consequence of the precipitation of these elements of the electrodes. The electrokinetic tests proved the functionality of the reactor, and the use of innovative elements contributed to these results
Keywords: Eletrocinética; Reator; Eletrodos; Electrokinetic; Reactor; Electrodes; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA